Green hope or red herring? Examining consumer perceptions of peer-to-peer energy trading in the United Kingdom. (October 2020) - Pumphrey, Kate; Walker, Sara Louise; Andoni, Merlinda; Robu, Valentin
Abstract: Across the globe, electricity sectors have seen a relatively large increase in the number of installations of small renewable energy systems, leading to an interest in the potential role of the prosumer. These prosumers (producers and consumers of electricity) could help drive electricity sector transformation, but at present electricity trading is associated with a lack of control and power held by consumers. Peer-to-peer trading schemes between energy consumers are increasingly being reported in the trade press as a new way to empower consumers, especially since the advent of blockchain, an emergent technology that could facilitate the adoption of such schemes. Research to understand how and why electricity trading occurs has received little attention within literature thus far. In this study we investigated the existing elements of electricity trading. A total of 16 structured interviews with domestic consumers, business consumers, domestic prosumers and business prosumers were undertaken. All interviews identified ease of payment as a key theme for electricity trading (although we note that ease may be in tension with sustainability and greater awareness of energy-related environmental impacts). Consumer interviews also identified lack of engagement with the process of receiving energy, and cost, as key themes. Prosumer interviews identified positive associations with power, and personal and business image, as key themes. Therefore, it is recommended that these factors be incorporated into the user interface of blockchain systems, to potentially increase adoption for peer-to-peer trading.